Developmental trajectories of executive functions in young males with fragile X syndrome. (October 2018) - Hooper, Stephen R.; Hatton, Deborah; Sideris, John; Sullivan, Kelly; Ornstein, Peter A.; Bailey, Donald B.
Highlights: Lower EF task completion. Lower performance on nearly all EF tasks. Slow rate of EF gains over time. Abstract: Background: Executive functions (EF) have been identified as impaired in FXS, but few studies have examined their developmental trajectories. Aims: The primary aim of this longitudinal study was to examine the development of EF in young males with FXS compared to Mental Age (MA)-matched controls. Methods and Procedures: The sample comprised 56 boys with FXS (ages 7–13 years), and 48 MA-matched typical boys (ages 4–8 years). EF tasks included measures of inhibitory control, working memory, cognitive flexibility/set-shifting, problem solving/planning, and processing speed. Tasks were administered at three time points over five-years. Outcomes and Results: The MA-Matched Typical boys significantly outperformed the FXS boys on all EF tasks, with the FXS Group showing a pattern of slow, but positive growth on most EF tasks. For working memory tasks, significant interactions were noted between MA and autism symptom severity, and MA and medication status. The probability of task completion increased with higher MA. Conclusions and Implications: These findings contribute to our understanding of the development of EF in this population. They also lay the foundation for use of EF tasks in treatment efforts, particularly with respect to documenting improvements and practice effects, and in understanding associations with targeted developmental outcomes.